Hierarchically carbon-coated Na3V2(PO4)3 nanoflakes for high-rate capability and ultralong cycle-life sodium ion batteries - Zhao, Yilin; Cao, Xinxin; Fang, Guozhao; Wang, Yaping; Yang, Hulin; Liang, Shuquan; Pan, Anqiang; Cao, Guozhong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Na3V2(PO4)3/C nanoflakes were synthesized by a solid-state reaction.•Span 80 acts both as surfactant and carbon resources.•The uniform nanoflakes can be controlled by the heating rates.•The carbon-coated NVP nanoflakes exhibit excellent electrochemical properties. Developing rechargeable sodium ion batteries (SIBs) with fast charge/discharge rate, high energy and power density, and long lifespan is still a significant challenge. Na3V2(PO4)3 (NVP) is regarded as one of the most potential SIBs cathodes due to its high theoretical capacity and stable sodium superionic conductor (NASICON) structure. However, the general NVP exhibits inferior electron conductivity due to the two separated [VO6] octahedral arrangement, which limits its widespread applications. Here, we present a design of hierarchical porous carbon-coated NVP nanoflakes via a facile molten hydrocarbon-assisted, solid-state reaction strategy, in which span 80 acts as surfactant and carbon source. The formation mechanism of this hierarchical open structure constructed by uniform nanoflakes was investigated by a heating-rate controlled experiment, which indicated that heating rates play an important role in morphology and structure of the final products. When used as SIBs cathode, the hierarchical porous carbon-coated NVP nanoflakes electrodes exhibited high reversible capacity of 114.2 mA h g−1 at 0.5 C, high rate capacity of 87.7 mA h g−1 at 100 C and excellent cyclic stability up to 10,000 cycles with only 0.0048% per cycling capacity fading, indicating the good sodium storage performances. This work demonstrates that the unique hierarchically porous flaky structure is favorable for improving the cyclability and rate capability in energy storage applications.